2004
DOI: 10.1210/jc.2003-032124
|View full text |Cite
|
Sign up to set email alerts
|

A Familial Form of Congenital Hypopituitarism Due to aPROP1Mutation in a Large Kindred: Phenotypic andin VitroFunctional Studies

Abstract: We report the natural history of a hypopituitarism in a large Tunisian kindred including 29 subjects from the same consanguineous family. The index case was a 9-yr-old girl with severe growth retardation due to complete GH deficiency and partial corticotroph, lactotroph, and thyrotroph deficiencies. Magnetic resonance imaging showed a hyperplastic anterior pituitary. Thirteen of the 28 relatives examined (10 female subjects) had hypopituitarism. In the 14 patients, previously untreated (aged 6-53 yr), height w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 30 publications
3
22
0
6
Order By: Relevance
“…The majority of these mutations are predicted to result in complete loss of function of the protein by ablating DNA binding and transcriptional activation. However, in vitro analysis has shown that some missense mutations retain partial activity (76,81,82). By far, the most common mutation (50-72% of all familial PROP1 mutations) (77,78,83), detected in multiple unrelated families from several different countries, is a 2 bp deletion among three tandem GA repeats ( 296 -GAGAGAG-302 ) within exon 2 resulting in a frameshift at codon 101 and the introduction of a termination codon at position 109 (often referred to as S109X), and probably represents a mutational hot spot within the gene, rather than a single common founder mutation (84).…”
Section: Prop1mentioning
confidence: 99%
“…The majority of these mutations are predicted to result in complete loss of function of the protein by ablating DNA binding and transcriptional activation. However, in vitro analysis has shown that some missense mutations retain partial activity (76,81,82). By far, the most common mutation (50-72% of all familial PROP1 mutations) (77,78,83), detected in multiple unrelated families from several different countries, is a 2 bp deletion among three tandem GA repeats ( 296 -GAGAGAG-302 ) within exon 2 resulting in a frameshift at codon 101 and the introduction of a termination codon at position 109 (often referred to as S109X), and probably represents a mutational hot spot within the gene, rather than a single common founder mutation (84).…”
Section: Prop1mentioning
confidence: 99%
“…This cell lineage is the most distinct among the pituitary cells (Reynaud et al 2004). In response to FGF8 signalling, corticotrope progenitors do not express any of the rostro-dorsal-specific TFs.…”
Section: Corticotropesmentioning
confidence: 98%
“…Skirtingų literatūros šaltinių duomenimis, izoliuoto hipopituitarizmo (arba izoliuoto augimo hormono deficito) paplitimas vertinamas nuo 1:4000 iki 1:10 000 gyvagimių dėl hipofizės gaminamo augimo hormono arba jo geno patologijos ir sąlygoja augimo sutrikimą (1)(2)(3)(4). Dauginis hipopituitarizmas (DHP) pasitaiko rečiau -1:8000 gyvagimių arba dar rečiau (5-7), bet jo klinikiniai simptomai yra ryškesni: tokiems pacientams kartu su augimo sutrikimu randama centrinė hipotirozė, hipogonadotropinis hipogonadizmas, gali išryš-kėti ir antrinis antinksčių nepakankamumas.…”
Section: Genetiškai Determinuotas Hipopituitarizmasunclassified
“…Šį geną sudaro trys egzonai, koduojantys 226 amino rūgščių baltymą. PROP-1 geno ekspresija yra reikalinga genų programos aktyvavimui, kuri indukuoja ventralinę hipofizės proliferaciją ir pagrindinių adenohipofizės ląstelių diferenciaciją (3,10).…”
Section: Genetiškai Determinuotas Hipopituitarizmasunclassified
See 1 more Smart Citation